2016
DOI: 10.1140/epjc/s10052-016-3892-4
|View full text |Cite
|
Sign up to set email alerts
|

NLO+NLL squark and gluino production cross sections with threshold-improved parton distributions

Abstract: We present updated predictions for the cross sections for pair production of squarks and gluinos at the LHC Run II. First of all, we update the calculations based on NLO+NLL partonic cross sections by using the NNPDF3.0NLO global analysis. This study includes a full characterization of theoretical uncertainties from higher orders, PDFs and the strong coupling. Then we explore the implications for this calculation of the recent NNPDF3.0 PDFs with NLO+NLL threshold resummation. We find that the shift in the resu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(78 citation statements)
references
References 144 publications
(207 reference statements)
1
77
0
Order By: Relevance
“…Prospino2 [93,101,105] and MadGolem [142][143][144] give predictions that are NLO-QCD accurate, while NLL-fast [145], NNLL-fast [146] and Resummino [147] also resum threshold logarithms. All codes, with the exception of MadGolem and Resummino, assume mass-degenerate squark spectra.…”
Section: Simulations and Cross Section Calculations In Susymentioning
confidence: 99%
“…Prospino2 [93,101,105] and MadGolem [142][143][144] give predictions that are NLO-QCD accurate, while NLL-fast [145], NNLL-fast [146] and Resummino [147] also resum threshold logarithms. All codes, with the exception of MadGolem and Resummino, assume mass-degenerate squark spectra.…”
Section: Simulations and Cross Section Calculations In Susymentioning
confidence: 99%
“…Including these contributions in the PDFs can produce non-negligible differences in threshold resummed cross section predictions when compared to those obtained with regular PDFs. An example of this can be found in [76], which considered sparticle pair production. In particular, for a large range of sparticle masses considered it was found that while K-factors (defined as the ratio of the resummed result to the fixed order one) obtained with regular PDFs were almost always greater than unity, this was not always the case when resummed PDFs were employed.…”
Section: B Comparison With Resummed Pdfsmentioning
confidence: 99%
“…In this contribution, we explore the impact of the LHCb data on the NNPDF3.1 analysis and show how sizable constraints are derived at large-x for all the light quark PDFs and for the charm PDF. In turn, this leads to reduced theoretical uncertainties for the production of new massive BSM resonances, which are dominated currently by the large-x PDF uncertainties [11].…”
Section: Pos(dis2017)198mentioning
confidence: 99%